Orbitally Forced Hyperstratification of the Oligocene South Atlantic Ocean. Issue 5 (23rd May 2018) - Liebrand, Diederik; Raffi, Isabella; Fraguas, Ángela; Laxenaire, Rémi; Bosmans, Joyce H. C.; Hilgen, Frederik J.; Wilson, Paul A.; Batenburg, Sietske J.; Beddow, Helen M.; Bohaty, Steven M.; Bown, Paul R.; Crocker, Anya J.; et al.
Abstract: Pelagic sediments from the subtropical South Atlantic Ocean contain geographically extensive Oligocene ooze and chalk layers that consist almost entirely of the calcareous nannofossil Braarudosphaera . Poor recovery and the lack of precise dating of these horizons in previous studies has limited the understanding of the number of acmes, their timing and durations, and therefore their likely cause. Here we present a high‐resolution, astronomically tuned stratigraphy of Braarudosphaera oozes (29.5–27.9 Ma) from Ocean Drilling Program Site 1264 in the southeastern Atlantic Ocean. We identify seven episodes with highly abundant Braarudosphaera . Four of these acme events coincide with maxima and three with minima in the ~110 and 405‐kyr paced eccentricity cycles. The longest lasting acme event corresponds to a pronounced minimum in the ~2.4‐Myr eccentricity cycle. In the modern ocean, Braarudosphaera occurrences are limited to shallow marine and neritic settings, and the calcified coccospheres of Braarudosphaera are probably produced during a resting stage in the algal life cycle. Therefore, we hypothesize that the Oligocene acmes point to extensive and episodic (hyper) stratified surface water conditions, with a shallow pycnocline that may have served as a virtual seafloor and (partially/temporarily) prevented the coccospheres from sinking in the pelagic realm. We speculate that hyperstratification was either extended across large areas of the South Atlantic basin, through the formation of relatively hyposaline surface waters, or eddy contained through strong isopycnals at the base of eddies. Astronomical forcing of atmospheric and/or oceanic circulation could have triggered these conditions through either sustained rainfall over the open ocean and adjacent land masses or increased Agulhas Leakage. Plain Language Summary: Sediment cores recovered from the South Atlantic Ocean contain several decimeter‐thick chalk layers. Scientific study of these recurrent chalk layers shows that 28.5 million years ago an enigmatic alga named Braarudosphaera proliferated in the surface ocean of the subtropical South Atlantic. In the modern day these algae only live in coastal waters, and their presence in the middle of the South Atlantic Ocean (far away from coasts) is a puzzle that oceanographers have attempted to solve for decades. We show that these algal blooms recurred when Earth's orbit changed seasonal conditions. We suggest that stratification of the South Atlantic surface Ocean in the geological past could have resulted in a density barrier (a "virtual" seafloor) that largely prevented these coastal algae from sinking. This would have enabled their widespread blooms and chalk formation in the open ocean. We speculate that either monsoons or eddies caused regional or local stratification. More research is needed into the life cycle of Braarudosphaera to fully determine whether these microfossil remains indeed signify stratification. Key Points: Seven astronomically forced open ocean Braarudosphaera acmes occurred during the mid‐Oligocene in the subtropical South Atlantic Ocean The exact paleoecologic, paleoceanographic, and paleoclimatic significance of the mid‐Oligocene Braarudosphaera acmes remains unclear Recurrent hyperstratification can provide a virtual seafloor, which may be required in Braarudosphaera 's life cycle